Morphology and anatomy of the developing fruit and seed of Dalechampia stipulacea Müll. Arg. (Euphorbiaceae) - DOI: 10.4025/actascibiolsci.v31i4.4834 (Acta Scientiarum. Biological Sciences, 2009)
In forest remnants of Maringá, Paraná, Brazil, there is abundance of the liana species, with little studied reproductive structures, morphologically and anatomically. Among these species occurs Dalechampia stipulacea Müll. Arg., which is the object of the present study. It is a Euphorbiaceae with pseudanthium and trichomes that cause irritation of the skin. The fruits and seeds were fixed and cut freehand and in a rotation microtome, according to the usual techniques. The fruit is a schizocarp tricocca with loculicidal and septicidal dehiscence. The mature pericarp presents sclerenchymatous middle mesocarp and endocarp that originate from meristems installed in the ovary mesophyll and epidermis. The inner mesocarp is constituted by a layer of macrosclereids of subepidermic origin. The seed originates from anatropous, bitegmic and crassinucelate ovule; it is exotegmic and albuminous. The seed presents structural characteristics verified in Acalyphoideae, except for the mesotegmen vascularization